Periods of formation and development of China's foreign policy concept (International relations and international law Journal, 2016)
China occupies a leading position in the world in terms of economic development, population growth and a number of other major socio-economic indicators. At the same time, the country remains unresolved complex problems inherent in developing countries. As a result, almost all the global risks, from the point of view of the authorities of the PRC, have a high degree of relevance. Taking action against them is considered, on the one hand, as a way to strengthen the country's position in the world, on the other – as a tool for internal development , enabling sustain high growth rates. Chinese’s foreign policy became a serious object to research for the broad circle of scientists and analysts. Its today trends are directly tied to PRC’s foreign-policy concepts in the period of 1960-1990’s. Coverage of these aspects seems quite important for the prediction of Chinese future policy. The article is based on Russian, Kazakh and Chinese materials.
Keywords: China; foreign policy; world order; Deng Xiaoping; hegemonism; security; multipolarity; regional stability